2010
DOI: 10.1074/jbc.m110.130120
|View full text |Cite
|
Sign up to set email alerts
|

Novel Phorbol Ester-binding Motif Mediates Hormonal Activation of Na+/H+ Exchanger

Abstract: Protein kinase C (PKC) is considered crucial for hormonal Na؉ /H ؉ exchanger (NHE1) activation because phorbol esters (PEs) strongly activate NHE1. However, here we report that rather than PKC, direct binding of PEs/diacylglycerol to the NHE1 lipid-interacting domain (LID) and the subsequent tighter association of LID with the plasma membrane mainly underlies NHE1 activation. We show that (i) PEs directly interact with the LID of NHE1 in vitro, (ii) like PKC, green fluorescent protein (GFP)-labeled LID translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 57 publications
(64 reference statements)
1
19
0
Order By: Relevance
“…Disruption of the interaction between the LID and the membrane strongly attenuated NHE1 activity. These data are compatible with a model in which interaction of the LID with the acidic inner plasma membrane leaflet plays a crucial role in NHE1 activity, and that tighter association of the LID with the membrane underlies NHE1 activation by diacylglycerol analogs [149]. In fact, regulation by interaction of the C-terminal tail with the inner membrane leaflet may be a conserved feature of the NHE family, since similar results were obtained in a recent study of NHE3 interactions with acidic phospholipids [150].…”
Section: Ii6 Nhe1 Interactions With Other Cellular Componentssupporting
confidence: 83%
“…Disruption of the interaction between the LID and the membrane strongly attenuated NHE1 activity. These data are compatible with a model in which interaction of the LID with the acidic inner plasma membrane leaflet plays a crucial role in NHE1 activity, and that tighter association of the LID with the membrane underlies NHE1 activation by diacylglycerol analogs [149]. In fact, regulation by interaction of the C-terminal tail with the inner membrane leaflet may be a conserved feature of the NHE family, since similar results were obtained in a recent study of NHE3 interactions with acidic phospholipids [150].…”
Section: Ii6 Nhe1 Interactions With Other Cellular Componentssupporting
confidence: 83%
“…However, significant binding was not observed between NHE1 and PS. A recent report demonstrated that a different C-terminal NHE1 peptide lipid-interacting domain (residues 542-598) bound multiple membrane phospholipids, including PS, using a different assay (31). Our data indicate that the N-terminal charged residues, some of which were deleted from the lipid-interacting domain, may be important for discriminating NHE1-phospholipid binding.…”
Section: Discussionmentioning
confidence: 71%
“…They found that the LID domain binds phorbol esters and used FRET reporters to show increased association of the NHE1 C terminus with the plasma membrane in cells treated with phorbol esters. However, phorbol ester and PI(4,5)P 2 binding within the LID may be distinct because alanine substitutions for Leu-573 and Ile-574 were identified as mediators of phorbol ester binding (36). Recent work from Schelling and co-workers (38) suggests that decreased NHE1 activity from disrupted PI(4,5)P 2 binding contributes to apoptosis in renal tubular atrophy.…”
Section: Ph-sensitive Phospholipid Binding Regulates Nhe1 Activitymentioning
confidence: 99%